Nepali Sign Language and Deaf Education Pedagogy in Nepal: Issues and Way Forwards - Sapkota, Sharada; Gautam, Bhim Lal (Nepalese Linguistics, 2025)
This paper explores the enduring issues and challenges in Deaf education and its pedagogical aspects in Nepal. The paper is based on the research that draws on primary data from interviews with native Nepali Sign Language (NSL) users, teachers, and parents, as well as Focus Group Discussions. Secondary sources include dictionaries, textual materials, videos, and research papers on NSL and other sign languages. The thematic approach was adopted to develop the paper from where various issues have been discovered. Issues such as the role of educational institutions, knowledge about Deaf language and culture, teacher recruitment, monitoring system and the physical facilities etc. are more pertinent than other basic issues. For this, the paper proposes various evidence-based strategies that implement bi/multilingual framework in order to highlight the critical role of introducing NSL from early childhood stage. Further, the paper recommends some policy issues related to sign language education in Nepal.